The Leadership of Employees in Management-Level: Case Study: Real Soluplus Co., Ltd. - ฟูกิจกาญจน์ โชติชวัล; งามกมล ชรินพร; ละอองนวล ประนอม (Business Administration and Management Journal Review, 2016)
The objectives of this research are to study leadership of managements of Real Soluplus Co., Ltd. before and after a seminar as well as to propose appropriate leadership for an organization. This research was a qualitative research and interview was used for data compilation. The findings reveal that the managers focused on each detail, set obvious goals, and had policies on confident making and incentives for employees. Some managers however work irrelevant to the plans and do as what they wanted to do. In addition, they did not put priority of jobs and not distribute jobs. They mainly focused on rules and not give important to incentives. They were not often receiving comments from employees and other managers. They persist in their opinions causing complicated work and eventually became one of weak points of the organization. The results after seminar obviously showed that the managers opened more opportunities for their employees to share their opinions. They put priority of jobs and distribute work. They better understood the difference between persons and focused on feelings of employees. The working environment therefore improved positively and led to appropriate leadership in an organization.